Enabling Faster Locomotion of Planetary Rovers With a Mechanically-Hybrid Suspension - Rodriguez-Martinez, David; Uno, Kentaro; Sawa, Kenta; Uda, Masahiro; Kudo, Gen; Diaz, Gustavo Hernan; Umemura, Ayumi; Santra, Shreya; Yoshida, Kazuya (IEEE robotics and automation letters, 2024)
The exploration of the lunar poles and the collection of samples from the martian surface are characterized by shorter time windows demanding increased autonomy and speeds. Autonomous mobile robots must intrinsically cope with a wider range of disturbances. Faster off-road navigation has been explored for terrestrial applications but the combined effects of increased speeds and reduced gravity fields are yet to be fully studied. In this paper, we design and demonstrate a novel fully passive suspension design for wheeled planetary robots, which couples for the first time a high-range passive rocker with elastic in-wheel coil-over shock absorbers. The design was initially conceived and verified in a reduced-gravity (1.625 m/s {^{2}} ) simulated environment, where three different passive suspension configurations were evaluated against steep slopes and unexpected obstacles, and later prototyped and validated in a series of field tests. The proposed mechanically-hybrid suspension proves to mitigate more effectively the negative effects (high-frequency/high-amplitude vibrations and impact loads) of faster locomotion ( \sim 1 m/s) over unstructured terrains under varied gravity fields.